(untitled) (Research, Society and Development, 2020)
The existance of human resources in an educational institution plays a very important role. Educators have great potential to carry out the activities of educational/ school institutions. The potential of every human resource in an educational/ school institution must be utilized as well as possible so as to be able to provide output/ graduates with optimal abilites.In this study it is known (X1), cmpensation (X1) has a significant effect, which is indicated by a significance value of 0.025 count less than 0.05 (5%), the variable Organizational Culture (X2) does not have a significant effect with a significant value of 0.208 greater from 0.05 (5%), work discipline (X3) with a significant value of 0.014 smaller than 0.05 (%) which means that work discipline effects the performance of Surabaya Shipping Polytechnic Educators.